2001
DOI: 10.1002/mds.1105
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism after glycine‐derivate exposure

Abstract: This 54-year-old man accidentally sprayed himself with the chemical agent glyphosate, a herbicide derived from the amino acid glycine. He developed disseminated skin lesions 6 hours after the accident. One month later, he developed a symmetrical parkinsonian syndrome. Two years after the initial exposure to glyphosate, magnetic resonance imaging revealed hyperintense signal in the globus pallidus and substantia nigra, bilaterally, on T2-weighted images. Levodopa/benserazide 500/125 mg daily provided satisfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 25 publications
1
33
0
4
Order By: Relevance
“…Both apoptosis and autophagy are involved in glyphosate toxicity mechanisms [29] Case reports indicated that exposure to glyphosate was related to Parkinsonism [19,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both apoptosis and autophagy are involved in glyphosate toxicity mechanisms [29] Case reports indicated that exposure to glyphosate was related to Parkinsonism [19,30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genotoxic activity [12], teratogenic activity [13], and disturbance of the normal gut bacterial community [14,15] due to glyphosate are reported. Glyphosate showed cytotoxic effects on different cells in vitro [16][17][18], and Barbosa et al [19], proposed that glyphosate may have contributed to the Parkinsonism due to its chemical similarity with glycine, a co-factor required for activation of the N-methyl-d-aspartase (NMDA) receptor, which controls excitatory actions in the central nervous system and is also involved in memory and learning. However, in clinical studies has not shown NMDA activity in relation to glyphosate poisoning [20].…”
Section: Introductionmentioning
confidence: 99%
“…This compound is of great interest because of its structural similarity to MPTP, a contaminant of synthetic heroin observed in the early 1980s to produce a parkinsonian syndrome in recreational drug users and subsequently used to investigate mechanisms involved in the etiology of PD (174). In addition to analytic studies, several case reports have described PD in individuals exposed to organophosphates (26, 78), glyphosate (17), paraquat (251), diquat (257), maneb (206), and other ethylene bis-dithiocarbamates (142). Higher concentrations of organochlorine residues, particularly dieldrin, have been found in postmortem brains of PD patients compared to patients with other neurological diseases (71,110).…”
Section: Neurologic Diseasementioning
confidence: 99%
“…Einerseits finden sich auch in diesen Fällen atypische Begleitbefunde (Diquat: [104]; Glyphosat: [3]), sodass entsprechend bisheriger klinischer Definition ein sekundäres PS vorliegt. Andererseits wurden z. T. auch lediglich funktionelle, d. h. reversible PS beobachtet, wiederum z. T. mit atypischen Begleitsymptomen (Organophosphate: [7,83]; Übersicht in: [7]).…”
Section: Der Mptp-unfallunclassified